The Relationship of Learning Interest to Science Online Learning Outcomes for Third-Grade Elementary School Students - Wiradarma, Komang Suardi; Suarni, Ni Ketut; Renda, Ndara Tanggu (Universitas Pendidikan Ganesha, 2021)
The difficulty of teachers in fostering student interest in online learning causes low student learning outcomes, especially in science learning. During the COVID-19 pandemic, learning in Indonesia was carried out online at every level of education, including at the elementary school level. So it takes a high student interest in learning to achieve maximum learning outcomes. This study aims to analyze the relationship between learning interest on science online learning outcomes. This type of research is ex post facto research. The number of populations and samples in this study was 60 students. Data collection techniques using a questionnaire. The data analysis used is simple regression and multiple regression using SPSS. The results showed that interest in learning and learning outcomes influenced each other. There was a significant positive correlation between interest in learning and student learning outcomes who scored Fcount > Ftable (0.302 > 0.254). So, there is a significant relationship between learning interest and online science learning outcomes for third grade students of Primary School Cluster III separately and simultaneously. The higher the student's interest in learning, the student's science learning outcomes will increase. The implication of this research is to improve teacher performance and the active role of parents to foster student interest in learning which will lead to improving student learning outcomes.